Malnutrition and parasitism shape ecosystem services provided by dung beetles - Mariana Servín-Pastor (Elsevier, 2021)
Ecosystem services relies on several insects that provide fundamental functions. Despite the quality of these ecosystem services depends on insect diversity, abundance and biomass, little is known about the effects that individual body condition has over such services. One prediction is that starving or sick animals may provide a reduced service. Dung beetles bury dung in forests and cattle farms, contributing to soil fertilization and reduction of greenhouse gas emissions from livestock. However, some species are highly sensitive to habitat disturbance and this leads to important losses of ecosystem services in disturbed areas. Here we experimentally tested the effect of diet quality and parasite pressure impact on dung removal rate using three species of dung beetles from contrasting habitats. We exposed wild beetles to an immune challenge combined with experimental diets that varied in protein content. We predicted that dung removal would be better carried out by healthy and well-fed individuals. However, if a species incurs in compensatory feeding or terminal investment in reproduction, ill individuals will still exhibit intense dung removal and reproductive activity but with a physiological cost. For Euoniticellus intermedius beetles, the immune challenge reduced dung removal rates, and this was because the challenge reduced the weight, although not the number of built brood masses. This suggests that implanted individuals made an intense reproductive effort. Therefore, a strategy of terminal investment in reproduction might be occurring. In the same species, couples fed low-protein diets increased dung removal rates compared to control-fed animals, probably as a compensatory feeding strategy that increased energetic condition. Conversely, Onthophagus incensus and O. rhinolophus beetles did not change dung removal rates despite suffering changes in energetic condition resulting from treatment. This is the first evidence that ecosystem services provided by dung beetles depend on individual health and nutritional status that drive reproductive and feeding behavior. Understanding the environmental factors that affect individual physiology and behavior is fundamental to guarantee conditions not only for the survival of key species but also for the maintenance of ecosystem services.